Topology optimization in structures with nonlinear behaviour - Oliveira, Riccardo (2019)
Optimization in engineering is the search for the optimal solution, taking into account the de ned design objective and the imposed constraints. There is a wide scope of applications in engineering, ranging from management and planning to structural design problems. The development of computers and programming has boosted this technology by enabling a faster and more e - cient search for optimal solutions through computational methods. Topology optimization combines the Finite Element Method (FEM) with optimization methods, in order to obtain the best distribution of material within a given domain. In this work, two distinct design objectives were analyzed in the scope of evaluation of non-linear structural problems: (i) minimization of compliance and (ii) minimization of complementary work. The material of the structure is described by a multi-linear behaviour (nonlinear elasticity) and a Solid Isotropic Material with Penalization (SIMP) approach. In order to solve the problem of topology optimization, a computational tool, enclosing a FEM analysis and a topology optimization algorithm, was developed using Matlab programming. The validation of the FEM was done using the numerical simulation program Abaqus as a reference, and, for the topology optimization problems, simulations were performed for several boundary conditions.